User Sentiment Analysis Towards Islamic Banking Applications in Indonesia - Arif Lubis, Fauzi (Journal of Islamic Economic and Business Research, 2024)
This study aims to analyze user sentiment towards Islamic banking applications in Indonesia, focusing on Islamic banking applications that have the lowest ratings on Google Playstore. The analysis was conducted to understand perceptions, satisfaction, and factors that influence user experience towards both applications in the context of Islamic economics. The research method used is a quantitative approach with sentiment analysis techniques on user reviews taken from Google Playstore. Data was collected by scraping user reviews and analyzed using the Natural Language Processing (NLP) method to identify positive and negative sentiments. In addition, descriptive analysis was used to explore the main themes that emerged in the user reviews. The results showed that the trust factor was the main contributor to positive sentiment, reaching 45.16% of the total positive sentiment. The feature factor was also significant, contributing 27.90%, while the Sharia aspect factor contributed 6.29%. The technical and service factors contributed 11.61% and 5.97%, respectively. These findings indicate that trust in the application, including security and integrity, as well as relevant features, is an essential element in shaping positive user sentiment. This study provides valuable insights for Islamic banking application developers and related parties to understand user needs and expectations. In addition, these findings highlight the importance of improving aspects of trust and application features to increase user satisfaction and loyalty. These findings contribute to the literature on Islamic economics and Islamic banking app development in the digital era and provide practical guidance to improve application performance in the Indonesian digital banking market.